2011
DOI: 10.1111/j.1365-2044.2011.06622.x
|View full text |Cite
|
Sign up to set email alerts
|

Three years’ experience of focused cardiovascular ultrasound in the peri‐operative period

Abstract: SummaryUltrasound applications in peri-operative medicine have become common place in modern anaesthesia practice. Anaesthetists have performed transoesophageal echocardiography in cardiac and selected non-cardiac surgery for over two decades. We aimed to assess the indications, impact on clinical management and accuracy of focused cardiovascular ultrasound performed by anaesthetists in the peri-operative period. One hundred and seventy patients over a 3-year period had a focused transthoracic echocardiogram. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 27 publications
4
92
1
3
Order By: Relevance
“…Conversely, a clinically unimportant finding or normal TTE had the effect of reassuring the anaesthetist, leading to a reduced requirement for further investigation, reduced invasive peri-operative monitoring and reduced postoperative level of care. The proportions of management changes were less than in three previous reports of peri-operative focused TTE [14,18,19], which could be due to differences in management definitions and patient cohorts.…”
Section: Discussioncontrasting
confidence: 72%
“…Conversely, a clinically unimportant finding or normal TTE had the effect of reassuring the anaesthetist, leading to a reduced requirement for further investigation, reduced invasive peri-operative monitoring and reduced postoperative level of care. The proportions of management changes were less than in three previous reports of peri-operative focused TTE [14,18,19], which could be due to differences in management definitions and patient cohorts.…”
Section: Discussioncontrasting
confidence: 72%
“…18 With appropriate training, these images can be interpreted with a high degree of correlation with expert assessment. 17,[19][20][21] Additionally, the technical skills needed for basic image acquisition can be successfully taught to trainees in anesthesiology using both simulation and curriculum implementation. [22][23][24] The knowledge base necessary for interpretation is based on pattern recognition and ''goalfocused'' assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] All the studies were reported as comprehensive examinations, which was reflected in the broad diversity of diagnoses. As described previously, preoperative exams occurred immediately prior to induction of anesthesia and data from pre-assessment clinic exams were not included.…”
Section: Resultsmentioning
confidence: 99%